43.3k views
2 votes
Answer this question ​

Answer this question ​-example-1
User Jane S
by
4.8k points

2 Answers

4 votes

Answer:

c) 120

Explanation:

f(x) = 7x^4 + 3x^2 - 4

f(-2) = 7(-2)^4 + 3(-2)^2 - 4 = 7(16) + 3(4) - 4 = 112 + 12 - 4 = 120

User Battech
by
5.2k points
1 vote

Answer:

120

Explanation:

Given,

x = -2

Now, let's solve


{7x}^(4) + 3 {x}^(2) - 4

Plug the value of x


= 7 * {( - 2)}^(4) + 3 * {( - 2)}^(2) - 4

A negative base raised to an even power equals a positive


= 7 * {2}^(4) + 3 * {2}^(2) - 4

Evaluate the power


= 7 * 16 + 3 * 4 - 4

Multiply the numbers


= 112 + 12 - 4

Add the numbers


= 124 - 4

Subtract the numbers


= 120

Hope this helps ...

Best regards!!

User Omer Tekbiyik
by
5.2k points